Human Digestive System: Gender-Based Contextual Teaching and Learning - Bustami, Yakobus; Utami, Yuniarti Essi; Supiandi, Markus Iyus; Elisabeth, Nyeria (FKIP Universitas Lampung, 2022)
The human digestive system is one of the materials taught to junior high school students. This research purpose was to determine the gender-based contextual (CTL) effect on biology students cognitive learning outcomes. This research used quasi-experimental design with pretest-posttest nonequivalent control group design. Data analysis used descriptive statistical and inferential statistics. The analysis results show that there was significant effect of using the CTL learning model on students' cognitive learning outcomes on the human digestive system material with sig value was 0.000>0.05. Regarding gender, there is no significant effect on cognitive learning outcomes on the human digestive system material with sig value was 0.764>0.05. There is no significant effect of the interaction of learning models and gender on cognitive learning outcomes on the human digestive system material with sig value was 0.960>0.05. Thus, the CTL learning model can improve the cognitive learning outcomes students who have gender characteristics.Keywords: human digestive system, contextual teaching and learning, cognitive learning outcomes, gender.DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1548-1560